OPTIMALISASI PENGGUNAAN APLIKASI WORDWALL DALAM MENINGKATKAN KREATIVITAS DAN MOTIVASI BELAJAR SISWA KELAS V PADA MATERI IPA DI SDN 22 PALU - Siti Zulqaidah; Achmad Ramadhan; Oktarafikayanti (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to optimize the use of the Wordwall application to enhance the creativity and learning motivation of fifth-grade students at SDN 22 Palu in science subjects. The research employed a Classroom Action Research (CAR) method conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection phases. The study involved 27 students as subjects. Data were collected through observations, interviews, and learning outcome tests, and were analyzed descriptively. The findings indicate a significant increase in students' motivation and creativity following the use of Wordwall. In the first cycle, students demonstrated limited enthusiasm, but by the second cycle, their engagement and motivation had increased significantly. The students' average scores also improved, surpassing the Minimum Mastery Criteria (KKM) in the second cycle. Additionally, the Wordwall application provided an interactive and enjoyable learning experience, stimulating students' creative thinking in understanding science concepts.